Libraries as Hybrid Space - Lawson, Keith (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper connects some trends and issues in planning and architecture with trends and issues in network design in order to consider the shape of hybrid space—created by the flowing together of spaces and networks. Referring to ideas of space articulated by Manuel Castells and to some of the… Cet article associe certaines tendances et questions touchant la planification et l’architecture, avec les tendances et enjeux de la conception de réseaux, afin d’examiner la configuration de l’espace hybride créée par la mise en commun des espaces et des réseaux. Référant à titre d’exemple aux idées formulées par Manuel Castells sur l’espace et à certaines des idées et composantes de…